2006
DOI: 10.1210/jc.2005-1651
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine Ablation of Thyroid Remnants after Preparation with Recombinant Human Thyrotropin in Differentiated Thyroid Carcinoma: Results of an International, Randomized, Controlled Study

Abstract: This study demonstrates comparable remnant ablation rates in patients prepared for 131I remnant ablation with 3.7 GBq by either administering rhTSH or withholding thyroid hormone. rhTSH-prepared patients maintained a higher quality of life and received less radiation exposure to the blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
236
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(264 citation statements)
references
References 22 publications
8
236
1
9
Order By: Relevance
“…In contrast, the results from this pivotal trial did show a significant and sizeable impairment in quality of life in the hypothyroid group compared with well-preserved quality of life in the rhTSH group (11). In the rhTSHstimulated group, the SF-36 score had increased from baseline in seven of eight domains by the time of ablation.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In contrast, the results from this pivotal trial did show a significant and sizeable impairment in quality of life in the hypothyroid group compared with well-preserved quality of life in the rhTSH group (11). In the rhTSHstimulated group, the SF-36 score had increased from baseline in seven of eight domains by the time of ablation.…”
Section: Introductionmentioning
confidence: 62%
“…This may include severe lethargy and fatigue,while enabling patients to remain euthyroid (7)(8)(9)(10). In addition, a multi-centre, randomised, controlled trial has directly compared the use of rhTSH preparation with the standard hypothyroid preparation, prior to remnant ablation with an activity of 3.7 GBq 131 I (11). Applying a pre-defined criterion to measure the success of ablation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Radioiodine doses in the range of 90 to 100 mCi 131 I are recommended when rhTSH is administered as an adjuvant before ablation (31,32). However, recent publications have shown that 50 mCi 131 I is equally effective to 100 mCi 131 I for thyroid remnant ablation following rhTSH, with no interruption in L-T 4 administration (33,34).…”
Section: Postoperative Radioiodine Administrationmentioning
confidence: 99%
“…Recent reports clearly demonstrate that rhTSH contributes considerably to reduce the dose to blood and bone marrow by shortening blood and whole-body residence times of 131 I [56][57][58].…”
Section: Therapy For Childhood Thyroid Cancermentioning
confidence: 99%